Short-Term Effects of Thoracic Spine Manipulation on the Biomechanical Organisation of Gait Initiation: A Randomized Pilot Study - Ditcharles, Sébastien; Yiou, Eric; Delafontaine, Arnaud; Hamaoui, Alain (Frontiers in Human Neuroscience, 2017)
Speed performance during gait initiation is known to be dependent on the capacity of the central nervous system to generate efficient anticipatory postural adjustments (APA). According to the posturo-kinetic capacity (PKC) concept, any factor enhancing postural chain mobility, and especially spine mobility, may facilitate the development of APA and thus speed performance. “Spinal Manipulative Therapy High-Velocity, Low-Amplitude” (SMT-HVLA) is a healing technique applied to the spine which is routinely used by healthcare practitioners to improve spine mobility. As such, it may have a positive effect on the PKC and therefore facilitate gait initiation. The present study aimed to investigate the short-term effect of thoracic SMT-HVLA on spine mobility, APA and speed performance during gait initiation. Healthy young adults (n=22) performed series of gait initiation trials on a force plate before (“pre-manipulation” condition) and after (“post-manipulation” condition) a sham manipulation or an HVLA manipulation applied to the ninth thoracic vertebrae (T9). Participants were randomly assigned to the sham (n=11) or the HVLA group (n=11).The spine range of motion (ROM) was assessed in each participant immediately after the sham or HVLA manipulations using inclinometers. Results showed that the maximal thoracic flexion increased in the HVLA group after the manipulation, which was not the case in the sham group. In the HVLA group, results further showed that each of the following gait initiation variables reached a significantly lower mean value in the post-manipulation condition as compared to the pre-manipulation condition: APA duration, peak of anticipatory backward centre of pressure displacement, centre of gravity velocity at foot-off, mechanical efficiency of APA, peak of centre of gravity velocity and step length. In contrast, for the sham group, results showed that none of the gait initiation variables significantly differed between the pre- and post-manipulation conditions. It is concluded that HVLA manipulation applied to T9 has an immediate beneficial effect on spine mobility but a detrimental effect on APA development and speed performance during gait initiation.We suggest that a neural effect induced by SMT-HVLA, possibly mediated by a transient alteration in the early sensory-motor integration, might have masked the potential mechanical benefits associated with increased spine mobility.